Pendidikan Keluarga Islam sebagai Landasan Iman Anak: Tinjauan Konseptual Tarbiyah Islamiyah - Affan Alwi Rezky (INKLUSIF: Jurnal Pendidikan Islam, 2025)
This article examines the role of Islamic education (Tarbiyah Islamiyah) within the family in building a strong foundation of faith in children. The family is viewed as the first and primary educational institution responsible for instilling Islamic creed (aqidah) from an early age, habituating acts of worship, and developing Islamic moral character in daily life. This study employs a library research method by analyzing primary and secondary sources, including the Qur’an, Hadith, classical Islamic scholars’ works, and contemporary literature on Islamic education. The findings indicate that the success of children’s faith education is strongly influenced by the synergy of affection, role modeling, and discipline within the family environment. These elements play a crucial role in internalizing Islamic values sustainably and strengthening children’s moral and spiritual resilience amid modern societal challenges. This study is expected to serve as a conceptual reference for developing holistic and relevant Islamic family education. Artikel ini membahas peran tarbiyah Islamiyah dalam keluarga sebagai upaya membentuk pondasi iman anak. Keluarga dipandang sebagai madrasah pertama yang memiliki tanggung jawab utama dalam penanaman aqidah sejak usia dini, pembiasaan ibadah, dan pembentukan akhlak Islami dalam kehidupan sehari-hari. Penelitian ini menggunakan metode library research dengan menganalisis berbagai sumber primer dan sekunder, meliputi Al-Qur’an, hadis, karya ulama klasik, serta literatur pendidikan Islam kontemporer. Hasil kajian menunjukkan bahwa keberhasilan pendidikan iman anak sangat dipengaruhi oleh sinergi kasih sayang, keteladanan, dan disiplin dalam lingkungan keluarga. Ketiga unsur tersebut berperan penting dalam menginternalisasikan nilai-nilai Islam secara berkelanjutan dan membangun ketahanan moral serta spiritual anak di tengah tantangan zaman modern. Penelitian ini diharapkan dapat menjadi rujukan konseptual bagi pengembangan pendidikan keluarga Islami yang holistik dan relevan.